Between the Superpowers: Some Remarks on the Role of Demons in Early Coptic Christianity. - Uljas, Sami; Landborg, Anne; Müller, Matthias (Vigiliae Christianae, 2021)
In early Coptic stories of saints and martyrs, demons are usually prototypical adversaries and side with the devil in his battle against Christ. However, it has been noted that in magical texts of a definitely Christian social origin, demons are sometimes invoked for assistance. Such sources might perhaps be dismissed as unrepresentative of the official theological position of the Alexandrian church, but, as is shown in the present paper, demons are occasionally portrayed as champions of Christ also in more 'respectable' texts such as hagiographies of the later 1st millennium AD. This is argued to show that the more nuanced analysis of demons does not represent an early folk undercurrent of Egyptian Christianity, but rather reflects an alternative theological view derived from the idea that God created good and evil for a reason.